Navigating a Covid World: The European Union's Internal Rebirth and External Quest. Issue 2 (3rd April 2021) - Alcaro, Riccardo; Tocci, Nathalie
ABSTRACT: The world on which Covid-19 has unleashed its destructive force is one where the partly supranational and multilateral-minded EU is ill at ease. The pandemic has devastated economies across the world and exacerbated pre-existing dynamics of growing geopolitical rivalry and the declining clout of multilateral regimes and practices. The EU's response to the Covid shock has been twofold: on the one hand, it has embarked on a new integration effort, with the contours of a 'transfer union' emerging for the first time in EU history; on the other hand, it has failed to use the crisis to advance its strategic autonomy agenda. The reason for this dichotomy is that, while the severity of the Covid emergency has shifted public and elite attitudes towards economic solidarity, the lingering commitment to the US has worked as a brake on a similar trend in European foreign policy preferences.